Strengthening Religious Character During the Covid-19 Pandemic Class III Elementary School: Penguatan Karakter Religius Pada Masa Pandemi Covid-19 Kelas III Sekolah Dasar - Nikmatul Alfiyah; Akhtim Wahyuni (Academia Open, 2022)
This study aims to describe the implementation of religious character habituation, obstacles in the habituation of religious characters and school solutions to overcome religious character obstacles that are applied during the covid-19 pandemic. The type of research below is a qualitative phenomology research. The research subjects were students, classroom teachers and parents. Data collection techniques used are observation, interviews, and documentation. In checking the validity of using a trust test, degree of accuracy, dependability test, and objectivity testing. Data analysis techniques are data reduction, data presentation, and data verification. The results of the study show that: 1) The implementation of strengthening religious character through habituation that is carried out routinely by students and by example. 2) Obstacles in the implementation of religious character habituation that are applied are the lack of student awareness, attention from parents, and infrastructure. 3) Solutions or efforts made by schools in overcoming obstacles to habituation of religious characters by carrying out order, supervision, providing examples, and socializing to students and parents.